PENGARUH PEMBERIAN MORFIN DOSIS LETHAL TERHADAP PERTUMBUHAN LARVA LALAT Chrysomya sp. PADA MEDIA BANGKAI TIKUS Rattus norvegicus GALUR WISTAR - Fadhlurrahman, Ahmad Reza; Baskoro, Aswin D; Permatasari, Nur (Jurusan Kedokteran FK Unsoed, 2013)
Death is the end of life. To identify unproper death on corpses, we use Post Mortem Interval (PMI). Insect evidence on the corpses can be used to estimate the Post Mortem Interval, however many factors including drugs may affect the rate of fly larva growth. Two rats with average BW 200 grams were used in this experimental study in order to analyze the influence of morphine on growth rate of fly larvae. One rat were given 120 grams of morphine orally (LD50 = 461mg/KgBW), and the other were killed by cervical dislocation and used as control. The rats were then simultaneously killed and caged individually into Chrysomya sp. cages to let the flies deposit their eggs on the rat corpses. Five developing larvae were sampled twice daily to determine the body length, weight and the growth rate until they were emerging to be adult. Result of this study showed that the length and the weight were lower and the growth of Chrysomya sp. larvae in rat corpses containing morphine were faster than control. The significant result occured at third stadium (p < 0,005) This result suggested that morphine can precipitate the growth rate of fly larvae.